Life Histories of Two Endangered Sea Skaters Halobates matsumurai Esaki and Asclepios shiranui (Esaki) (Hemiptera: Gerridae: Halobatinae) - Terumi Ikawa; Yuichi Nozoe; Natsuko Yamashita; Namiko Nishimura; Satoshi Ohnoki; Kyoko Yusa; Sugihiko Hoshizaki; Masayuki Komaba; Akihiro Kawakubo (Psyche: A Journal of Entomology)
Sea skaters Halobates matsumurai Esaki and Asclepios shiranui (Esaki) are among the few marine insects found in Japan. For the past several decades, they have become rare in most localities and have now been designated as endangered by the government. In order to understand their adaptive strategies to the marine environment and to develop conservation measures, it is essential to know their life histories. We studied their lifecycles in Kujukushima Bay off the north coast of Kyushu (Japan) where they co-occurred in small coves along the jagged coast. They appeared to have more than one generation a year and to overwinter in the egg stage. Eggs of H. matsumurai were laid on natural sandstones and man-made sandstone walls along the shore, mostly above the average sea level. The eggs had very hard shells, presumably adaptive to protect them from desiccation, solar radiation, and wave action, especially during the overwintering period.